Reaksi Pasar Saham terhadap Pengumuman Penerbitan Obligasi Syariah di Bursa Efek Indonesia - PRIMADANI, RESI (Jurnal Ilmu Manajemen (JIM), 2013)
Announcement of the sharia bonds issuance give a signal to investors in making investment decisions to buy or sell a stock. Actions of investors in making decisions to buy or sell a stock will affect the demand and supply on the company’s stock issuer of the sharia bonds so that it is possible the abnormal return of the increase or decrease in the stock price. This study used event study to determine whether there is stock market reaction around the announcement date of the sharia bonds issuance in Indonesia Stock Exchange. The results of these hypothesis with paired sample t-test showed that there was no difference before the announcement date and after the announcement date of the sharia bonds issuance. In conclusion, there is no stock market reaction to the announcement of the sharia bonds issuance in Indonesia Stock Exchange. Keywords: Stock Market Reaction, Sharia Bonds Issuance, Event Study.